2014
DOI: 10.1111/gcb.12626
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, biochemical, and genome‐wide transcriptional analysis reveals that elevated CO2 mitigates the impact of combined heat wave and drought stress in Arabidopsis thaliana at multiple organizational levels

Abstract: Climate changes increasingly threaten plant growth and productivity. Such changes are complex and involve multiple environmental factors, including rising CO2 levels and climate extreme events. As the molecular and physiological mechanisms underlying plant responses to realistic future climate extreme conditions are still poorly understood, a multiple organizational level analysis (i.e. eco-physiological, biochemical, and transcriptional) was performed, using Arabidopsis exposed to incremental heat wave and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
140
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 105 publications
6
140
0
Order By: Relevance
“…oxidative pressure (Farfan-Vignolo and Asard, 2012;Naudts et al, 2014;Zinta et al, 2014 Phosphorous being a major constituent of nucleic acid (about 40-60% P in the cell), P deficiency affects RNA synthesis and protein synthesis, and thus inhibits metabolism including photosynthesis. Optimum photosynthesis requires 2.0-2.5 mM P is required in the chloroplast.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…oxidative pressure (Farfan-Vignolo and Asard, 2012;Naudts et al, 2014;Zinta et al, 2014 Phosphorous being a major constituent of nucleic acid (about 40-60% P in the cell), P deficiency affects RNA synthesis and protein synthesis, and thus inhibits metabolism including photosynthesis. Optimum photosynthesis requires 2.0-2.5 mM P is required in the chloroplast.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Many experiments have been carried out to study the responses of plants to high [CO 2 ] at various levels ranging from the ecosystem to the genome (e.g. Ainsworth and Long 2005;Luo et al, 2006;Teng et al, 2006;Niu et al, 2011;Dieleman et al, 2012;AbdElgawad et al, 2014;Zinta et al, 2014). Such studies revealed that elevated [CO 2 ] increases plant growth and crop yield by the stimulation of carboxylation and suppression of oxygenation activity of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) particularly in C3 plants, whereas the effects are marginal in C4 plants because Rubisco is already saturated at ambient [CO 2 ] (reviewed by Bowes 1991;Ghannoum et al, 2003;Feng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, for hsp21 mutants, other protective processes such as efficient reactive oxygen species (ROS) detoxification, improved redox homeostasis and decreased photorespiration as consequences of CO 2 enrichment might occur. 8 Together, this work indicates that NPR1-mediated SA signaling is important for basal thermotolerance; however, NPR1 is not required for elevated CO 2 -induced HS mitigation in Arabidopsis. Elevated CO 2 could ameliorate HS-induced deleterious effect on photosynthetic apparatus without involvement of HSP21, but basal thermotolerance as well as elevated CO 2 -induced HS tolerance largely depends on HSP70-1 in Arabidopsis.…”
mentioning
confidence: 70%
“…7 Previous studies indicate that elevated CO 2 could minimize HS-induced deleterious effects on plants. 7,8 Nonetheless, the mechanisms of elevated CO 2 -induced HS mitigation are unknown. Previously, we have demonstrated that elevated CO 2 -induced HS mitigation does not involve abscisic acid-dependent process in tomato.…”
mentioning
confidence: 99%
See 1 more Smart Citation